Construction of pseudotyped human coronaviruses and detection of pre-existing antibodies in the human population - Qi Jiang; Xi Wu; Fangyu Dong; Shan Qiao; Qiaoyun Shi; Changyong Jian; Chen Chen; Jiuyue Zhou; Youchun Wang; Weijin Huang (Biosafety and Health)
In order to clarify the pre-exist immunity background of different human coronaviruses (HCoV), this study investigated the positive rate of spike (S) protein antibodies of HCoV, including HCoV- severe acute respiratory syndrome (SARS) −associated coronavirus (SARS-CoV-1), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), Middle East respiratory syndrome coronavirus (MERS-CoV), HCoV-229E, HCoV-NL63, HCoV-HKU1 and HCoV-OC43, before and after the Coronavirus Disease 2019 (COVID-19) outbreak. We utilized pseudotyped virus-based neutralization assays (PBNA) or enzyme-linked immunosorbent assays (ELISA) to detect antibody levels against HCoV in serum samples collected in 2009–2010 and 2023. The PBNA results showed that neutralizing antibodies against SARS-CoV-1 and the MERS-CoV were negative. In the serum samples from 2009 to 2010, neutralizing antibodies against SARS-CoV-2 (D614G) were negative, whereas in the serum samples from 2023, 73 samples (73 %) showed neutralizing reactions with the SARS-CoV-2 D614G strain, 96 samples (96 %) with the BA.5 strain, and 91 samples (91 %) with the BF.7 strain. Among pre-COVID-19 samples, 33 % (33/100) showed neutralizing reactions with HCoV-229E and 63 % (63/100) with HCoV-NL63. Among post-COVID-19 samples, 50 % (50/100) showed neutralizing reactions with HCoV-229E and 49 % (49/100) with HCoV-NL63. Due to the different receptors of alpha coronavirus genus compared to other beta coronavirus genus, neutralizing antibodies against HCoV-OC43 and HCoV-HKU1 virus cannot be detected by constructing corresponding pseudotyped virus. Binding antibodies against HCoV-OC43 and HCoV-HKU1 virus were detected using ELISA. The results revealed that among pre-COVID-19 samples, 83 % (83/100) and 45 % (45/100) had binding activity with HCoV-OC43 and HCoV-HKU1, respectively. Among post-COVID-19 samples, 100 % (100/100) and 81 % (81/100) had binding activity with HCoV-OC43 and HCoV-HKU1, respectively.